Tenaga buruh dan upah dalam Islam: satu pandangan alternatif - Mansor Jusoh; Nor Ghani Md. Nor (Penerbit Universiti Kebangsaan Malaysia, 2005)
Labour is but one of the many resources owned by a human being. The concept allows labour to be considered as an input in production process without necessarily implying that labourers are slave to another human being. Overpopulation and surplus labour can be a problem in any country with rapid population growth. The fact that Allah S.W.T is the all provider of sustenance does not necessarily mean that a country embracing the Islamic economic system is free from the problems. The claim that wages should be paid according to work and quality of labour has not found strong support in Islam. On the contrary Islam prefers wages to be determined through .musyawarah. which can be interpreted as a bargaining process between employer and employee in the labour market. Another Islamic principle that wages should at least satisfy the basic living requirements is not inconsistent with a market system and thus can be implemented. However, its implimentation in an Islamic economy may be expected to differ from that practiced in a capitalist economy